2013
DOI: 10.1523/jneurosci.4479-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate-Induced Nociceptor Excitation and Ongoing Pain Behavior in Mice and Humans Is Largely Mediated by S1P3 Receptor

Abstract: The biolipid sphingosine-1-phosphate (S1P) is an essential modulator of innate immunity, cell migration, and wound healing. It is released locally upon acute tissue injury from endothelial cells and activated thrombocytes and, therefore, may give rise to acute posttraumatic pain sensation via a yet elusive molecular mechanism. We have used an interdisciplinary approach to address this question, and we find that intradermal injection of S1P induced significant licking and flinching behavior in wild-type mice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(114 citation statements)
references
References 61 publications
11
102
1
Order By: Relevance
“…A key function of S1P 1 and S1P 3 occurs during inflammatory disease processes through the promotion of astrogliosis (75,76). S1P receptor signaling induces nociceptive responses, possibly as a result of local increases of S1P, which are induced by injury or inflammation and sensed by S1P 3 (35,(77)(78)(79). Overall, the transport and biological functions of S1P in the nervous system are not well understood.…”
Section: S1p Metabolismmentioning
confidence: 99%
“…A key function of S1P 1 and S1P 3 occurs during inflammatory disease processes through the promotion of astrogliosis (75,76). S1P receptor signaling induces nociceptive responses, possibly as a result of local increases of S1P, which are induced by injury or inflammation and sensed by S1P 3 (35,(77)(78)(79). Overall, the transport and biological functions of S1P in the nervous system are not well understood.…”
Section: S1p Metabolismmentioning
confidence: 99%
“…Although analyses of entire mouse dorsal root ganglion found that S1P 3 was the most highly expressed S1PR, single cell mRNA analysis of individual neurons found that S1P 1 was most highly expressed, regardless of neuronal subtype, indicating that high expression of S1P 3 occurs in ganglion cell types other than neurons ( Fig. 5 ) ( 131,132 ). One group found that pain responses induced by intradermal S1P injection or models of postoperative pain were signifi cantly decreased in S1pr3 Ϫ / Ϫ mice, whereas minimal differences were seen in S1pr1 Ϫ / Ϫ mice ( 131 ); however, another group found that mice lacking S1P 1 specifi cally in nociceptor neurons were protected from S1P-induced pain ( 133 ).…”
Section: Nervous Systemmentioning
confidence: 99%
“…For example, intra-as well as extracellular-applied S1P facilitates NGF-induced excitability of sensory neurons from dorsal root ganglia (DRG) (Zhang et al, 2006a,b) and induces thermal hyperalgesia (Mair et al, 2011). Accordingly, injection of S1P in peripheral tissue elicits hyperalgesic responses either directly through neuronal expressed S1P receptors S1P1 and S1P3 (Mair et al, 2011;Camprubi-Robles et al, 2013) or indirectly through immune cells such as neutrophil granulocytes (Finley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%